Corruption as an Extra-Ordinary Crime: Elements and Eradication Efforts in Indonesia - Yunus, Nur Rohim; Nasution, Latipah; Romlah, Siti; Nurhalimah, Siti (Journal of Creativity Student, 2021)
Corruption is part of the extraordinary crime. This is because corruption has threatened the country's economy, democracy, and public welfare. Prevention and prosecution of extraordinary crimes need to be carried out in an extraordinary way as well. This study uses a normative type of research, with a statutory approach and a literature approach. The results of the study state that the establishment of the Corruption Eradication Commission is a tool used by the Indonesian government in implementing law enforcement. Additional punishment is an effort to crack down on corruption crimes. In fact, handling corruption cases requires cooperation between law enforcement officials, the government and the community.